1952
DOI: 10.1039/jr9520002657
|View full text |Cite
|
Sign up to set email alerts
|

503. Studies in the polyene series. Part XLIII. The structure and synthesis of vitamin A2 and related compounds

Abstract: A dehydrovitamin A, (11) has been synthesized and shown to be identical with vitamin A,. The aldehyde (retinene,) and anhydrovitamin A,, both crystalline solids, have been prepared from the synthetic vitamin. The ultra-violet and infra-red light absorption properties of these and related compounds with shorter side-chains are discussed. A preliminary account of this work has been published (Chem. and Ind., 1951, 49).THE presence in fish-liver oils of a compound closely related to vitamin A, was first indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar treatment of 3-dehydroretinol (3,4-didehydroretinol) with ethanolic HCI gives anhydrovitamin A2, exhibiting similar absorption bands in the u.v. region (Shantz, 1948;Farrar et al, 1952). Further studies by Henbest et al (1955) have shown that anhydrovitamin A2 may have a 3-ethoxyanhydroretinol or 3-methoxyanhydroretinol structure, depending on the nature of the solvent used in its preparation.…”
mentioning
confidence: 99%
“…Similar treatment of 3-dehydroretinol (3,4-didehydroretinol) with ethanolic HCI gives anhydrovitamin A2, exhibiting similar absorption bands in the u.v. region (Shantz, 1948;Farrar et al, 1952). Further studies by Henbest et al (1955) have shown that anhydrovitamin A2 may have a 3-ethoxyanhydroretinol or 3-methoxyanhydroretinol structure, depending on the nature of the solvent used in its preparation.…”
mentioning
confidence: 99%